창업가의 개인적 특성과 기술 기반 창업기업 성과 간의 관계에서 사회적 네트워크의 매개효과 - 신은영; 이주연 (시스템엔지니어링학술지, 2024)
The purpose of this study is to identify the influence of entrepreneurs’ personal characteristics on the performance of technology-based Firms through the components of social networks, thereby providing basic data that can help improve the performance of technology-based companies. To this end, research questions were presented, and the results of the study using statistical analysis through an online Google survey are summarized as follows. First, there was a positive correlation between the Big 5 components of personal characteristics and the size and strength of social networks. Second, the size of the social network completely mediated the relationship between entrepreneurs’ personal characteristics of extroversion and performance, and the size partially mediated the relationship between agreeableness, conscientiousness, and neuroticism and performance. However, openness was found to have no mediating effect on the relationship with performance, and strength was found to have a partial mediating effect on the relationship between personal characteristics of extroversion, agreeableness, conscientiousness, and neuroticism. Therefore, in order to improve the performance of entrepreneurs, it is necessary to promote a tailored government support project that takes into account the size and strength of social networks by utilizing personal characteristics such as extroversion, agreeableness, conscientiousness, and neuroticism.
Keywords: Creator; Personal Characteristics; Technological Entrepreneurship; Social Networking; Mediating Effect